Altered lipid metabolism as a possible mechanism in fumonisin-induced hepatocarcinogenesis in rats and investigations into risk assessment in humans - Burger, Hester Maria (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.